PABRIK FOSFOR TRIKLORIDA DARI FOSFOR DAN GAS KLORIN KAPASITAS 20.000 TON/TAHUN - , ANNISA PRIMANINGTYAS ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Phosphorus trichloride is produced by elemental reaction of liquid phosphorus with chlorine gas in the bubble reactor. The reaction is spontaneous at 1 atm and the temperature of 90 o C. The reaction is exothermic, hence for keeping the isothermal process, cooling process is required to take the heat that is formed. Phosphorus trichloride plant is designed with a capacity of 20,000 tons / year. The raw materials are phosphorus 4602.12 tons/year and chlorine 3208.56 tons/year. The plant will be established in Cilegon, Banten, with the required area are approximately 23.92 acres and the workers are 145 peoples. The required utilities for supporting this process are 119,898.94 m 3 /year of water, 600 kW of power, 59.21 m 3 /3 days of the diesel fuel and 496,748.5 m 3 /year of fuel oil. The result of economic analysis are Rp116.072.755.300,00 + US$10,143,609.19 of the fixed capital